Aqueous Chemical Synthesis of Ln2Sn2O7 Pyrochlore‐Structured Ceramics. Issue 9 (3rd June 2013) - Kong, Linggen; Karatchevtseva, Inna; Blackford, Mark G.; Scales, Nicholas; Triani, Gerry; Vance, E.
<x xml:space="preserve">Abstract</x> Pyrochlore‐structured lanthanide stannate ceramic (Ln2Sn2O7) has been synthesized via a new complex precipitation method. A suite of characterization techniques, including FTIR, Raman, X‐ray, and electron diffraction as well as nitrogen sorption were employed to investigate the structural evolution of the synthesized and calcined powder. Raman, XRD, and selected area electron diffraction results confirm the presence of the pyrochlore structure after calcination of the powder above 1200°C. TEM imaging shows fine crystallites gradually increased in size from approximately 100 nm to about 500 nm with higher calcination temperatures. Grain growth and powder densification upon increasing the calcination temperature was confirmed by nitrogen sorption results. This aqueous synthetic method provides a simple pathway for the preparation of homogeneous lanthanide stannate ceramics.